L’ANALYSE JURILINGUISTIQUE EN TRADUCTION, EXERCICE DE DROIT COMPARÉ. TRADUIRE LA LETTRE OU «L’ESPRIT DES LOIS»? LE CAS DU CODE NAPOLÉON - GÉMAR, Jean-Claude (Comparative Legilinguistics, 2019)
Translated texts sometimes reflect the targeted legal system’s conventional manner of writing law; however, the equivalence of the legal message must be realized. Translating law into another legal culture goes through a comparative analysis of the laws involved, the command of which is needed to achieve legal equivalence. The form of the target text must nevertheless correspond to its legal culture. Legal translation is then the meeting point of languages, cultures and laws. To succeed, this meeting must be based on an ad hoc knowledge of both laws. Then comparative law enters into play as the legal translator’s “fellow traveler”, whom it equips for the exchange. To realize it, “two intersecting receptions will suffice” (Carbonnier). This operation is successful when concepts and notions overlap and the letter of the law (the substance) and the law’s expression (the form) merge, demonstrating “the spirit of the laws”. Benchmarking is the way to reach this goal. It is conducted here under the light of jurilinguistics via the analysis of terms and concepts presenting various translation difficulties, which demonstrate the necessity of comparative law (I). A comparison of translations of the Napoleonic Code and other civil codes will complete the quest for the spirit of the laws by the way in which the letter or the spirit of the text to be translated is rendered (II). The lessons to be learned are aimed at language professionals, who will find in jurilinguistic comparative analysis a way to perfecting their work and, in the translations of the civil codes, a basis of reflection on the role and functions of translation.